(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Peri-operative pain management is a very crucial entity as it decides the morbidity and outcome of the patient’s post-surgery. Optimal pain relief helps early mobilization and discharge. Oral medications are not permitted in early post-operative period and therefore, injectable analgesia is the most commonly employed to treat pain. With the understanding of pain pathophysiology and newer routes of drug administration, efforts are being put to benefit the patients with adequate pain relief with maximum action of drug and minimal systemic effects so that when administered via a suitable route, it is also complaint with the patient. Methods: In a similar effort we conducted a study on 100 patients belonging to ASA I and II grades, age between 18- 60 years, either gender, posted for elective inguinal hernia surgeries under spinal anesthesia for comparing the analgesic effects of diclofenac transdermal patch 100 mg and diclofenac intramuscular injection 75 mg. The participants were randomly divided into 2 groups of 50 each: group DP who received diclofenac patch and group DI who received intramuscular injection diclofenac, using computer generated random number table. Hemodynamic parameters such as heart rate, systolic blood pressure, diastolic blood pressure was noted in perioperative period. Comparison of the duration of post operative analgesia in both the study groups by assessing VAS score and hemodynamic response to pain was done. The time and requirement of total number of recue analgesia in both study groups was noted. Injection tramadol 2 mg/kg was given when VAS score was more than 3 in the first 24 hours. Adverse effects like: Nausea, Gastritis, Vomiting, Erythema, Pruritis were looked for after administration of the study drugs. Results: The change in mean VAS was found to be similar over the timeline in both the groups with p value > 0.05. The pattern of change between the groups was also found to be similar with P value of more than 0.05. 16% in group DP and 96% in group IM required rescue analgesia within 24 hours. Among the participants in group DP, 16% had duration of 4 hours and 84% had duration of 24 hours or more. Among those in group DI, 84% had duration of 6 hours and 16% had analgesia for 24 hours or more. The duration was significantly more in patch group than in the IM injection group with p value of less than 0.05. Administration as transdermal patch produced a smaller number of systemic side effects than IM injection and showed fewer local side effects. Conclusions: It was concluded that, transdermal diclofenac patch 100 mg, as a pre-emptive analgesic is beneficial and can be a useful alternative to IM diclofenac 75 mg in patients undergoing inguinal hernia correction surgeries under subarachnoid block. Although the onset of action of diclofenac patch takes time to achieve its peak plasma concentration as compared to diclofenac injection, the patch has an advantage because of its ease of application, self-administration and self-termination, fewer local side effects, no systemic side effects, bypasses the first pass metabolism in the liver, can be used in patients who are nil per oral post operatively thus having a better patient compliance.